Stability of the mitochondrial genome requires an amino-terminal domain of yeast mitochondrial RNA polymerase - Wang, Yuanhong (The National Academy of Sciences, 1999)
Mitochondrial RNA (mtRNA) polymerases are related to bacteriophage RNA polymerases, but contain a unique amino-terminal extension of unknown origin and function. In addition to harboring mitochondrial targeting information, we show here that the amino-terminal extension of yeast mtRNA polymerase is required for a mtDNA maintenance function that is separable from the known RNA polymerization activity of the enzyme. Deletion of 185 N-terminal amino acids from the enzyme results in a temperature-sensitive mitochondrial petite phenotype, characterized by increased instability and eventual loss of the mitochondrial genome. Mitochondrial transcription initiation in vivo is largely unaffected by this mutation and expression of just the amino-terminal portion of the protein in trans partially suppresses the mitochondrial defect, indicating that the amino-terminal extension of the enzyme harbors an independent functional domain that is required for mtDNA replication and/or stability. These results suggest that amino-terminal extensions present in mtRNA polymerases comprise functional domains that couple additional activities to the transcription process in mitochondria.